Risk factors for reoperation after discectomy of lumbar herniated intervertebral disc disease - Cheng-Huan Peng; Ing-Ho Chen; Tzai-Chiu Yu; Jen-Hung Wang; Wen-Tien Wu; Kuang-Ting Yeh (Tzu Chi Medical Journal)
Objectives: Discectomy is the most common surgery for lumbar herniated intervertebral disc (HIVD) disease. However, 5%–24% of patients undergo a second surgery due to recurrent disc herniation. Materials and Methods: This study was aimed to identify the risk factors for reoperation after discectomy of lumbar HIVD and recommend treatment for patients with a high risk of reoperation. We recruited patients diagnosed as having single-level lumbar HIVD who underwent open discectomy from January 1, 2000, to December 31, 2012 in our hospital. We used a survival curve to inspect the survival time and reoperation rate after surgery. We discussed the correlation of reoperation rate with discectomy level, body mass index, heavy lifting after surgery, sex, and age. Furthermore, we investigated the correlation between the experience of a surgeon and the reoperation rate. Results: A total of 619 patients were enrolled in our study. Most patients were 40–60 years old (48.8%), and most of them had herniation at L4/5 level (48.9%). The 8-year survival rate was 92%. Weight lifting after surgery may increase the reoperation rate by 115 and 18 times for those >60 years and <40 years, respectively. In addition, less experience of the surgeon and female sex had a high reoperation rate. Conclusion: Postoperative working modification may be very important for preventing patients from recurrent HIVD. For elderly people with HIVD, a more conservative therapy could be selected. If patients with lumbar spine hypermobility or severe degeneration require wide laminectomy, primary fusion should be considered.